2012
DOI: 10.5194/amt-5-2843-2012
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of MetOp-A/IASI CO profiles and validation with MOZAIC data

Abstract: Abstract. The IASI (Infrared Atmospheric Sounding Interferometer) nadir-looking thermal infrared sounder onboard MetOp-A enables the monitoring of atmospheric constituents on a global scale. This paper presents a quality assessment of IASI CO profiles retrieved by the two different retrieval algorithms SOFRID and FORLI, by an intercomparison with airborne in-situ CO profiles from the MOZAIC program for the and upper tropospheric partial column (480-225 hPa) comparisons as well as profile comparisons are made.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…Previous validation studies using ground-based, aircraft and satellite data have shown that CO total columns from MOPITT and IASI are retrieved with an error generally below 10-15 % at mid and tropical latitudes, but can have larger errors in polar regions (MOPITT: Deeter et al, 2012Deeter et al, , 2013Emmons et al, 2004Emmons et al, , 2009IASI: George et al, 2009;Pommier et al, 2010;De Wachter et al, 2012;Kerzenmacher et al, 2012). The profiles are only weakly resolved, with < 1 to ∼ 2.5 independent pieces of information, depending mostly on the thermal state of the atmosphere.…”
Section: Retrieved Co Productsmentioning
confidence: 99%
“…Previous validation studies using ground-based, aircraft and satellite data have shown that CO total columns from MOPITT and IASI are retrieved with an error generally below 10-15 % at mid and tropical latitudes, but can have larger errors in polar regions (MOPITT: Deeter et al, 2012Deeter et al, , 2013Emmons et al, 2004Emmons et al, , 2009IASI: George et al, 2009;Pommier et al, 2010;De Wachter et al, 2012;Kerzenmacher et al, 2012). The profiles are only weakly resolved, with < 1 to ∼ 2.5 independent pieces of information, depending mostly on the thermal state of the atmosphere.…”
Section: Retrieved Co Productsmentioning
confidence: 99%
“…The spectra are processed in near-real time, and the CO profiles are distributed with error covariance, averaging kernels and quality flags information (www.pole-ether.fr). The IASI CO product was validated against ground-based observations (Kerzenmacher et al, 2012), aircraft data (De Wachter et al, 2012), and satellite measurements ). The FORLI-CO column (v20100815) values used here are daytime data.…”
Section: Iasi Atmospheric Columnsmentioning
confidence: 99%
“…Section 6 provides a summary and conclusions. (Eremenko et al, 2008;Barret et al, 2011) and CO De Wachter et al, 2012). In the present study, we use data provided by the Software for a Fast Retrieval of IASI Data (SOFRID) presented in Barret et al (2011) for O 3 and in De Wachter et al (2012) for CO.…”
Section: Introductionmentioning
confidence: 99%